THE ETHICS OF ACCOUNTING STUDENTS: A COMPARATIVE STUDY - Dian Indri Purnamasari (Journal of Economics, Business, and Accountancy Ventura, 2011)
It is noted that there have been problems of ethics in the auditing happening in big companies.In addition, the issues of ethics are closely related to the auditing profession. This isbelieved that they are also related to the independence in doing the profession. In consequence,the auditing profession is expected to have high independency and objectivity becauseit has the responsibility for providing public service to the society who has trustedthem. A professional accounting begins his or her career at accounting school as a student.Therefore, this study intends to answer the question of the ethics among the accounting students.Again, this study intends to examine the ethics of the accounting students by makingthe comparison among the accounting students of public universities and privates universities,as well as at the Accounting Profession Education Program (PPA). Besides that, it alsocompares the male and female accounting students. The results show that that gender doesnot influence the student’s choosing the alternative answers of either B or C, but influencesthem to choose the alternative of A. Further analysis also indicates that the male studentshave bigger probability to accept the offer to violate the existing ethics and not to tell anyonethan their counterparts. It is due to the condition that the male students take more risks orface challenge in doing their job than their counterparts.